Chronic disease management support in Australian workplaces—low base, rising need. (8th January 2018) - Saunders, Carla; Brown, James J.; Carter, David J.; Lapkin, Sam
Abstract: Issue addressed: This study investigates the current nature, levels and perceived need for workplace support among mature age Australian workers with chronic illness. Methods: A cross‐sectional population survey was conducted via a double opt‐in panel sample of Australian workers aged 45 years and older with one or more of six major chronic diseases (diabetes and/or chronic heart, kidney, lung, mental health and/or musculoskeletal conditions). Results: Three hundred and fourteen respondents reported being in the workforce and having at least one of the chronic conditions under investigation, of which almost one third reported having more than one of the conditions. The findings reveal a number of considerable gaps in Australian workplace support for employees 45 years and older with chronic illness, including workplace flexibility, supportive policies and co‐worker support. Conclusions: This research adds to a scarce existing literature base on workplace support for workers with chronic illness in Australia. Future research is needed to identify opportunities for effective public policy and implementation of workplace interventions to better support this cohort. So what?: If timely progress is not made in this area, the projected increase in the aged population and scheduled public policy changes impacting retirement age will multiply potential adverse effects on the health of employees with chronic illness and Australia's labour market productivity.